Multiple linear regression models to simulate spore yields of Bacillus amyloliquefaciens BS13 through optimization of medium composition. (18th January 2022) - Kamoun, Fakher; Weekers, Frederic; Ayed, Rayda Ben; Mechri, Sondes; Jabeur, Fadoua; Thonart, Philippe; Jaouadi, Bassem
Abstract: Bacillus amyloliquefaciens is a food spoilage spore‐forming bacterium. Its spores are useful for multiple biotechnological applications. Nevertheless, few reports are available regarding the achievement of a high cell density and good sporulation effectiveness under fermentation conditions. Therefore, the current study was designed to optimize a low‐cost fermentation medium allowing the highest sporulation yield by B. amyloliquefaciens strain BS13. Our data revealed that tryptone and starch were the best carbon and energy sources. In addition, two nitrogen sources namely, corn steep liquor (CSL) and yeast extract (YE), allowed a significant enhancement of spore production and they were both retained for further optimization. A combination of CaCl2, MgSO4, and MnSO4 showed a positive impact on spores' production. The composition of the optimized medium was (in g/L); tryptone 3, starch 15, CSL 13.5, YE 1.5, CaCl2 0.1, MgSO4 ·7H2 O 0.012, and MnSO4 ·7H2 O 0.0012. Such medium was further validated in a 400‐L fermentor. The spore yield by B. amyloliquefaciens strain BS13 was enhanced from 3.0 × 10 10 spores/mL under flask culture conditions to 6.2 × 10 10 spores/mL when cultures were performed on large scale. Therefore, strain BS13 spore preparation could be proposed as a promising probiotic and a biocontrol agent useful for plants, animals, and humans. Abstract : Graphical abstract: